Pengaruh Faktor Harga dan Kepercayaan Terhadap Minat Pelanggan dalam Membeli Produk DRW Skincare - Muhammad Rama Rizaldi; Tegar Dwi Fajriatama; Abdul Yusuf (Economic Reviews Journal, 2024)
Scientific study articles from the library as part of Marketing Management Science are the influence of online marketing, customer trust, brand image, and customer satisfaction on purchasing decisions and customer loyalty. The purpose of this article is to investigate the impact of price and trust on consumers' willingness to purchase DRW Skincare products. This research suggests that trust has a positive and significant impact on interest in purchasing DRW Skincare products. Apart from that, the price factor has a positive & significant influence on the interest in buying the product. This descriptive analysis is quantitative for this research method, which uses SPSS tools. The results of this article are: 1) product prices can be compared with their quality. 2): product marketing influences customer loyalty. 3): Brand perception influences customer interest in purchasing products.